Use of radiation from PC screen for non-destructive controlling the internal strains in transparent parts - Maslov, V.P.; Kachur, N.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
It is known that the most widely used method to control internal strains is the
optical polarization method. However, the sources of polarized radiation are the most
problem issue of this method. There are some difficulties in using this method when
testing large-scale optical parts, diameters of which exceed 500 mm. To choose an
optical source suitable for solving these tasks, we have analyzed the design of liquidcrystal
screens and ascertained the possibility to use their polarized radiation in tests of
internal strains in optical parts of large dimensions. Adduced below are the results of
investigations of internal strains in parts of sapphire and organic glass.